Outcome of 609 adults after relapse of acute lymphoblastic leukemia (ALL); an MRC UKALL12/ECOG 2993 study. - Fielding, A; Richards, S; Chopra, R; Lazarus, H; Litzow, MR; Buck, G; Durrant, I; Luger, S; Marks, D; Franklin, I; McMillan, A; Tallman, MS; et al. (2007)
Most adults with acute lymphoblastic leukemia (ALL) who achieve complete remission (CR) will relapse. We examined the outcome of 609 adults with recurring ALL, all of whom were previously treated on the Medical Research Council (MRC) UKALL12/ECOG2993 study, where the overall survival (OS) of newly diagnosed patients is 38% (95% confidence interval [CI]=36%-41%) at 5 years. By contrast, OS at 5 years after relapse was 7% (95% CI=4%-9%). Factors predicting a good outcome after salvage therapy were young age (OS of 12% in patients younger than 20 years vs OS of 3% in patients older than 50 years; 2P<.001) and short duration of first remission (CR1) (OS of 11% in those with a CR1 of more than 2 years versus OS of 5% in those with a CR1 of less than 2 years; 2P<.001). Treatment received in CR1 did not influence outcome after relapse. In a very highly selected subgroup of patients who were able to receive HSCT after relapse, some were long-term survivors. We conclude from a large, unselected series with mature follow-up that most adults with recurring ALL, whatever their prior treatment, cannot be rescued using currently available therapies. Prevention of recurrence is the best strategy for long-term survival in this disease.